The even Greater Commission: Relating the Great Commission to the missio Dei, and human agency to divine activity, in mission - Konz, D. J. (Missiology, 2018)
This article proposes a means to reconcile and properly order two of the dominant missiological concepts of the past century: the so-called "Great Commission" of Matthew 28:18-20, and the concept of missio Dei. By doing so, the article seeks to offer a more robustly trinitarian basis for mission which references the Great Commission, and a means to better nuance and understand the relationship between divine and human agency in mission. To make these arguments, the article offers a theological primer on and critique of the two missiological concepts, then contends that the Great Commission should be understood as a second-order, rather than a first-order, frame of reference for mission, located within the wider trinitarian framework of the "even greater" co-missions of the Son and Spirit. The article then draws on the theology of Karl Barth to affirm that the church, insofar as its actions correspond to God's own activity in the Spirit, can be regarded as the locus of human co-activity in the pneumatological missio of God. With further reference to Barth, the article proposes that properly ordering and relating the Great Commission and the missio Dei allows for a cooperative, if asymmetrical, co-missional account of the relation between God's agency and human action in mission. While primarily drawing on the resources of systematic theology, the article concludes with some preliminary implications for mission theology and practice.